2001
DOI: 10.1080/13691180110069455
|View full text |Cite
|
Sign up to set email alerts
|

Community e-gateways: locating networks and learning for social inclusion

Abstract: A b s t r a c tThe provision of community e-gateways (community-based facilities providing public access to computers and the Internet) has been seen as a way to address the 'digital divide', particularly for people from deprived neighbourhoods. In the UK, policy and practitioner literature has stressed that for these centres to be successful they need to have strong social connections and be able to provide opportunities for interactive learning and content creation. Through a detailed analysis of one communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…While a persuasive case can undoubtedly be made for being open to the potential benefits of the Internet for families with disabled children, there are also grounds for being cautious. There is currently concern about a range of people who may fall on the wrong side of the ‘digital divide’ because they do not have Internet access and experience (Policy Action Team 15 2000; Hellawell 2001; Liff & Steward 2001). These tend to be people from the most socially excluded, financially deprived sectors of the population.…”
Section: Introductionmentioning
confidence: 99%
“…While a persuasive case can undoubtedly be made for being open to the potential benefits of the Internet for families with disabled children, there are also grounds for being cautious. There is currently concern about a range of people who may fall on the wrong side of the ‘digital divide’ because they do not have Internet access and experience (Policy Action Team 15 2000; Hellawell 2001; Liff & Steward 2001). These tend to be people from the most socially excluded, financially deprived sectors of the population.…”
Section: Introductionmentioning
confidence: 99%
“…The first two conditions are also present in the housing cooperative. Most importantly, according to Mehra et al (2004), Myles (2004) and Selwyn (2006), both groups have found ways of using and colonizing the web that make sense to them as individuals (Liff and Steward, 2001) and communities. Interests such as local politics and campaign contacts were clear motivators towards the use of the internet in these communities (see also music, books, baseball in Newholm et al, 2004).The third and fourth conditions provide the basis for efficient teamwork and are likely to be present in communities, but it is the fifth that gives the slack that allows them to respond in a discretionary manner to the needs of the tenants.To the extent that this successfully engages the tenants in ICT, we might refer to this loosely as optimal slack.This would not be remarkable, but for being able to imagine it to be relatively rare.…”
Section: Discussionmentioning
confidence: 99%
“…The context in which training and support is delivered is also of relevance here. As Liff and Steward (2001) argue, there must be a low access threshold and it should be provided within 'a context in which people feel comfortable about using it' (Liff et al, 1999: 2). Research conducted into barriers to learning for marginalized groups (Pierce, 2004), including transient people (Doherty et al, 2002) supports this notion.The former narrative illustrates how formal training can reflect the underlying causes of exclusion (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Community informatics scholars draw upon symbolic interactionist concepts when they focus on the interactions between people and technology. Liff and Steward (2001) analyzed the relationships between stakeholders in a CTC, concluding that interactions were not sufficient to sustain the center. Qiu (2009) focused on interactions between people and technologies to create a subgroup of working class Chinese people.…”
Section: Interactionist Paradigmmentioning
confidence: 99%